Direksi Hakim atau Kepatuhan Hukum: Analisis Dasar Pertimbangan Putusan Bebas dalam Perkara Korupsi di Pengadilan Tipikor Bengkulu: Judicial Discretion or Legal Compliance: A Basic Analysis of Considerations for Acquittals in Corruption Cases at the Bengkulu Corruption Court - Tari Corisa Ariani Putri; Alauddin; Ependi (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This research seeks to examine the basis of judicial reasoning behind the acquittal of defendants in corruption cases at the Bengkulu Corruption Court. The research employs an empirical legal approach using interviews, observation, and literature review techniques. hese problems underscore a disparity between normative legal standards and actual judicial practices, thereby impacting the effectiveness of anti-corruption initiatives at the regional level. hese problems underscore a disparity between normative legal standards and actual judicial practices, thereby impacting the effectiveness of anti-corruption initiatives at the regional level.. The challenges identified include a lack of independent witnesses, incorrect application of legal articles, and administrative irregularities during court proceedings. These problems underscore a disparity between normative legal standards and actual judicial practices, thereby impacting the effectiveness of anti-corruption initiatives at the regional level. The study recommends improving inter-agency coordination among law enforcement bodies and enhancing judicial capacity in handling corruption cases.